分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
设\(z = u{e^v}\),\(u = x + y\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}(1 + xy + {y^2})\) B: \({e^{xy}}(1 + xy + {y^3})\) C: \({e^{xy}}(x+ xy + {y^2})\) D: \({e^{xy}}(y+ xy + {y^2})\)
设\(z = u{e^v}\),\(u = x + y\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}(1 + xy + {y^2})\) B: \({e^{xy}}(1 + xy + {y^3})\) C: \({e^{xy}}(x+ xy + {y^2})\) D: \({e^{xy}}(y+ xy + {y^2})\)
(5). 由随机事件的分解性质,事件 \( \{XY=2\} \) 等价于( )。 A: \( \{X=1,Y=2\} \) B: \( \{X=2,Y=1\} \) C: \( \{X=1,Y=2\}\cap \{X=2,Y=1\} \) D: \( \{X=1,Y=2\}\cup \{X=2,Y=1\} \)
(5). 由随机事件的分解性质,事件 \( \{XY=2\} \) 等价于( )。 A: \( \{X=1,Y=2\} \) B: \( \{X=2,Y=1\} \) C: \( \{X=1,Y=2\}\cap \{X=2,Y=1\} \) D: \( \{X=1,Y=2\}\cup \{X=2,Y=1\} \)
下列方程中( )是一阶线性微分方程。 A: \( 2{x^2}yy' = {y^2} + 1 \) B: \( xy' + {y \over x} - x = 0 \) C: \( \cos y + x\sin y { { dy} \over {dx}} = 0 \) D: \( y'' + xy' = 4{x^2} + 1 \)
下列方程中( )是一阶线性微分方程。 A: \( 2{x^2}yy' = {y^2} + 1 \) B: \( xy' + {y \over x} - x = 0 \) C: \( \cos y + x\sin y { { dy} \over {dx}} = 0 \) D: \( y'' + xy' = 4{x^2} + 1 \)
应力圆的半径是( )。 A: (σx +σy)/2 B: (σx -σy)/2 C: τxy D: sqrt( [(σx -σy)/2]^2 + τxy^2 )
应力圆的半径是( )。 A: (σx +σy)/2 B: (σx -σy)/2 C: τxy D: sqrt( [(σx -σy)/2]^2 + τxy^2 )
已知:()x()-()y()=()1(),()z()-()y()=()2(),则()xy()+()yz()+()zx()-()x()2()-()y()2()-()z()2()的值是
已知:()x()-()y()=()1(),()z()-()y()=()2(),则()xy()+()yz()+()zx()-()x()2()-()y()2()-()z()2()的值是
积分[img=136x52]1803d6afd4e6f95.png[/img]的计算程序和结果是 A: clearsyms xy=1/x^2/sqrt(x^2-1)int(y,x,-2,-1)3^(1/2)/2 B: clearsyms xint(1/x^2/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 C: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)-pi/3 D: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 E: clearsyms xint(1/x^2*sqrt(x^2-1),x,-2,-1)log(3^(1/2) + 2) - 3^(1/2)/2
积分[img=136x52]1803d6afd4e6f95.png[/img]的计算程序和结果是 A: clearsyms xy=1/x^2/sqrt(x^2-1)int(y,x,-2,-1)3^(1/2)/2 B: clearsyms xint(1/x^2/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 C: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)-pi/3 D: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 E: clearsyms xint(1/x^2*sqrt(x^2-1),x,-2,-1)log(3^(1/2) + 2) - 3^(1/2)/2
方程\(\left( {1 - {x^2}} \right)y - xy' = 0\)的通解是( )。 A: \(y = C\sqrt {1 - {x^2}} \) B: \(y = - {1 \over 2}{x^3} + Cx\) C: \(y = {C \over {\sqrt {1 - {x^2}} }}\) D: \(y = Cx{e^{ - {1 \over 2}{x^2}}}\)
方程\(\left( {1 - {x^2}} \right)y - xy' = 0\)的通解是( )。 A: \(y = C\sqrt {1 - {x^2}} \) B: \(y = - {1 \over 2}{x^3} + Cx\) C: \(y = {C \over {\sqrt {1 - {x^2}} }}\) D: \(y = Cx{e^{ - {1 \over 2}{x^2}}}\)
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
\({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{xy}{x^2+y^2}\)= A: 0 B: 1 C: 1/2 D: 不存在
\({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{xy}{x^2+y^2}\)= A: 0 B: 1 C: 1/2 D: 不存在